The Relationship between Exercise Addiction and Satisfaction with Life in Physical Education and Sport Department Students - Hazar, Kürşat; Şenbakar, Kubilay (Asian Journal of Education and Training, 2020)
This study, conducted to analyze the relationship between exercise dependency and satisfaction with life in physical education and sport department students, is designed in a quantitive research model and a scanning pattern is used. The students of Physical Education and Sports Teaching Department, Coaching Education Department, Sports Management Department and Recreation Department in the Faculty of Sports Sciences of Fırat University voluntarily participated in the study. Personal information form, exercise addiction scale, and life satisfaction scale are used as data collection instruments. The obtained data have been evaluated in SPSS 24 Packet program and paired and multiple comparisons have been made according to the determined independent variables (Independent Groups t-Test, ANOVA), and Pearson Correlation analysis has been performed to examine the relationship between the variables. According to the findings, there is a significant difference between the participants’ sports year variable and life satisfaction (p<0.05). In addition, while there is a significant difference (p<0.05) in favor of recreation students regarding the department variable; it is found that the difference between the participants’ exercise addiction scale (EAS) and total number of days of doing sports, and years of sports and the average of academic scores are statistically significant (p<0.05). As a result; it has been concluded that as the year and duration of sports increase in physical education and sports department students, exercise dependence and life satisfaction levels increase, this increase positively affects the life satisfaction of the recreation department students and negatively affects the academic achievement of students.